Chiral phosphoric acid catalysis: from numbers to insights. (22nd January 2018) - Maji, Rajat; Mallojjala, Sharath Chandra; Wheeler, Steven E.
Abstract : Chiral phosphoric acids (CPAs) have emerged as powerful organocatalysts for asymmetric reactions, and applications of computational quantum chemistry have revealed important insights into the activity and selectivity of these catalysts. Abstract : Chiral phosphoric acids (CPAs) have emerged as powerful organocatalysts for asymmetric reactions, and applications of computational quantum chemistry have revealed important insights into the activity and selectivity of these catalysts. In this tutorial review, we provide an overview of computational tools at the disposal of computational organic chemists and demonstrate their application to a wide array of CPA catalysed reactions. Predictive models of the stereochemical outcome of these reactions are discussed along with specific examples of representative reactions and an outlook on remaining challenges in this area.